EKSPLORASI PERSEPSI SISWA TERHADAP PEMBELAJARAN PJOK MATERI PERMAINAN BOLA BASKET MELALUI PENDEKATAN TPACK DI SMP MUHAMMADIYAH 7 PROGRAM UNGGULAN COLOMADU - Muhammad Irfan Fatkhun Niam; Muhad Fatoni; Pungki Indarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Physical Education learning, particularly in basketball, is often perceived as difficult and less engaging by students. The integration of technology through the Technological Pedagogical Content Knowledge (TPACK) framework is considered a promising approach to enhance students’ understanding, motivation, and participation by balancing content, pedagogy, and technology. This study explores students’ perceptions of basketball learning through the TPACK approach at SMP Muhammadiyah 7 Colomadu and identifies key factors influencing perceptual changes. A descriptive qualitative design was employed using purposive sampling involving ten students (six male, four female) aged 13–15 years. Data were collected through semi-structured interviews, classroom observations, and documentation, analyzed using the Miles, Huberman, and Saldana model. Findings revealed a significant shift from negative to positive perceptions after TPACK implementation. The integration of interactive videos, visualized demonstrations, and digital evaluations enhanced comprehension, motivation, and active engagement. The TPACK approach effectively improves students’ understanding, motivation, and participation in basketball learning. Further quantitative or mixed-method studies are recommended to strengthen the validity and generalizability of these findings.